Secondary Metabolites Content and Effects of Zuriat Fruit (Hyphaene Thebacia) Brewing on the Reduction of Blood Glucose and Histopathology of β-Pancreatic Cells of Male Mice (Mus musculus) - Ni Wayan Sukma Antari; Ida Ayu Manik Damayanti; Ni Luh Adi Satriani (Indonesian Journal of Global Health Research, 2026)
Diabetes mellitus is caused by genetic factors, such as having a family history of the disease, being overweight (obesity), autoimmune diseases, and abnormalities in pancreatic β-cells. This study was conducted to examine the secondary metabolite content and effects of Zuriat fruit (Hyphaene Thebacia) infusion on reducing blood glucose and histopathology of pancreatic β-cells in male mice (Mus musculus). The results were analyzed using powder weights of 2 g/kg body weight and 5 g/kg body weight. This study employed a true experimental study design in a laboratory setting, where the research was conducted rigorously, controlling all factors that could interfere with internal validity. The study design used a posttest-only control group design, where the test was conducted after treatment. The results were processed using the One-Way ANOVA test. Administering a brew of zuriat fruit (Hyphaene thebacia) with a powder weight of 2 grams and 5 grams can reduce blood glucose levels in male mice. Administration of a brew of zuriat fruit (Hyphaene thebacia) with a powder weight of 2 grams and 5 grams can increase pancreatic β-cells. Administering zuriat fruit infusion has been shown to lower blood glucose levels in male mice compared to the control group.